Exploring the Impact of Sibling Dynamics on Emotional and Behavioral Growth - Ningrum, Luh De Kusuma (Yayasan Sinergi Kawula Muda, 2024)
Sibling relationships significantly influence children's cognitive, social, and emotional development, yet the complexity of these interactions requires further exploration. This study conducts a comprehensive review of existing literature to examine the role of sibling dynamics in shaping adaptive behaviors, emotional regulation, and social competence. A systematic search was performed across databases including Scopus, Google Scholar, and PubMed, utilizing keywords such as